1999
DOI: 10.1254/jjp.79.257
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) and Its Regulation by Ovarian Steroids in Rat Uterine Stromal Cells

Abstract: The effects of ovarian steroids on the expression of granulocyte-macrophage colony-stimulating factor (GM-CSF) in rat uterus were examined. Intense expression of GM-CSF mRNA was dispersedly located in the endometrial-myometrial junction and stroma of the uterus. GM-CSF was immunohistochemically localized in stromal cells and luminal epithelium. Ovariectomy significantly reduced the appearance of GM-CSF-mRNA-positive cells and the levels of expression for GM-CSF mRNA in the whole uterus, whereas treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…13 Additionally, both these cell types make GM-CSF. 11 The chemokine and cytokine environment that exists in the female reproductive tract and the means through which it drives neutrophil functional activation have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Additionally, both these cell types make GM-CSF. 11 The chemokine and cytokine environment that exists in the female reproductive tract and the means through which it drives neutrophil functional activation have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords: chemotaxis; granulocyte-macrophage colony-stimulating factor; interleukin-8; N-formyl-methionyl-leucyl-phenylalanine; mitogen-activated protein kinase; signalling 9 GM-CSF is produced by the tissues of the female reproductive tract 10 and its synthesis is now known to be hormonally regulated, at least in rodents. 11 Female reproductive tract tissues that produce IL-8 are also reported to produce GM-CSF. Indeed, we showed in an earlier report that the potent chemoattractant properties of female reproductive tract epithelial cell secretions were a result of synergy between IL-8 and GM-CSF produced by epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The tissues were parraffinembedded using a paraffin infiltration device (Tissue Tec VIP; Miles and Sankyo Co., Ltd., Tokyo), and the cross sections at 4-µm intervals were prepared on poly-L-lysine-coated slides (Matsunami, Kishiwada) (16). Ca in tissues was stained by the von Kossa method (17).…”
Section: Tissue Preparation and Staining By The Von Kossa Methodsmentioning
confidence: 99%
“…Recently, increasing evidences have suggested that GM‐CSF works as a potentially important mediator for intercellular communication in reproduction. The cyclic expression of GM‐CSF in endemetrium controlled by ovarian steroid hormones has been reported 4 . In human endometrium, mRNA expression of GM‐CSF reaches a peak in mid‐secretory phase 5 .…”
Section: Introductionmentioning
confidence: 99%